Fracture Load of Metal, Zirconia and Polyetheretherketone Posterior CAD-CAM Milled Fixed Partial Denture Frameworks - Rodríguez, Verónica (Materials (Basel), 2021)
The aim of this study was to investigate the load to fracture and fracture pattern of prosthetic frameworks for tooth-supported fixed partial dentures (FPDs) fabricated with different subtractive computer-aided design and computer-aided manufacturing (CAD-CAM) materials. Materials and Methods: Thirty standardized specimens with two abutments were fabricated to receive three-unit posterior FDP frameworks with an intermediate pontic. Specimens were randomly divided into three groups (n = 10 each) according to the material: group 1 (MM)—milled metal; group 2 (L)—zirconia; and group 3 (P)—Polyetheretherketone (PEEK). The specimens were thermo-cycled and subjected to a three-point bending test until fracture using a universal testing machine (cross-head speed: 1 mm/min). Axial compressive loads were applied at the central fossa of the pontics. Data analysis was made using one-way analysis of variance, Tamhane post hoc test, and Weibull statistics (α = 0.05). Results: Significant differences were observed among the groups for the fracture load (p < 0.0001). MM frameworks showed the highest fracture load values. The PEEK group registered higher fracture load values than zirconia samples. The Weibull statistics corroborated these results. The fracture pattern was different among the groups. Conclusions: Milled metal provided the highest fracture load values, followed by PEEK, and zirconia. However, all tested groups demonstrated clinically acceptable fracture load values higher than 1000 N. PEEK might be considered a promising alternative for posterior FPDs.